Research on the Inheritance and Innovation of Craftsman Spirit in the Training of Skilled Talents in Higher Vocational Colleges in the Post-epidemic Era - Zhu, Xiaolan; Liu, Bo; Kou, Heung (Journal of Educational Research and Policies, 2025)
In the post-pandemic era, vocational colleges face new challenges and opportunities in the training of skilled talents. This article provides an in-depth analysis of the training of skilled talents and the inheritance and innovation of craftsmanship in educational practice. By interpreting the current educational background, the article explains the new trend of development in vocational colleges and the impact of the pandemic on the training methods and content of skilled talents. Furthermore, it reveals the importance and essential requirements of craftsmanship in the training of skilled talents, and proposes the necessity of integrating craftsmanship into the process of training skilled talents. This article mainly discusses the ways of inheriting and innovating craftsmanship to meet the demands of the new era, aiming to provide theoretical support and practical guidance for vocational colleges in cultivating skilled talents that can adapt to social development. The research results show that combining the strategies of inheriting craftsmanship in teaching reform and curriculum development not only helps enhance students' professional skills and innovation abilities but also strengthens their sense of professional identity and responsibility.